2016
DOI: 10.1080/09613218.2016.1181874
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory incentives for green buildings: gross floor area concessions

Abstract: Incentive schemes formed by regulatory or administrative instruments are measures to promote green building (GB) and increase the motivation of developers to meet higher standards. The hidden costs to different stakeholders during the GB transaction are often ignored. Understanding these hidden transaction costs (TCs) helps appraise the costs and benefits of GB and policy effectiveness. The example of a gross floor area (GFA) concession scheme is used systematically to explore and understand the fundamental is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…Incentive policies are considered as the most important strategy for the advancement of GBTs adoption. This finding confirms the viewpoints of various researchers [30][31][32] that incentive schemes are very crucial for the promotion of green building developments. Financial incentives provide a valuable economic support for the industry, particularly individual stakeholders or firms, in the adoption process of GBTs which usually involves higher investment than adopting traditional building technologies.…”
Section: Analysis Results and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Incentive policies are considered as the most important strategy for the advancement of GBTs adoption. This finding confirms the viewpoints of various researchers [30][31][32] that incentive schemes are very crucial for the promotion of green building developments. Financial incentives provide a valuable economic support for the industry, particularly individual stakeholders or firms, in the adoption process of GBTs which usually involves higher investment than adopting traditional building technologies.…”
Section: Analysis Results and Discussionsupporting
confidence: 80%
“…There is consensus in the literature that these rating systems and labeling programs are instrumental in furthering the use of GBTs and practices [26][27][28][29]. Scholars have also argued that financial and regulatory incentive schemes are of great importance to the successful adoption of GBTs and practices [30][31][32][33]. Häkkinen and Belloni [34] further claimed that developing the awareness of clients about the benefits of green buildings is one of the most essential actions to encourage green building.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The framework of costs and benefits in this study expands the ones in previous research from Qian et al [44] and Fan et al [14] by adding more data through an extra 10-20 expert interviews. The initial framework of costs and hidden benefits were built using a literature review, same as the ones in Qian et al [44], shown in Table 2.…”
Section: Initial Framework Of Costs and Benefitssupporting
confidence: 48%
“…The prescribed building features are tailored for the specific built environment in Hong Kong to address the urgent city problems [59]. To some extent, it is mandatory to integrate the features in order to apply for the GFA concession [44]. For the Hong Kong government, few construction costs of these building features could improve the built environment.…”
Section: Gfa Concession Scheme In Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation